How to schedule surgical operations into operating rooms? An application in Turkey - Koksalmis, E.; Hancerliogullari, K.O.; Hancerliogullari, G. (Institute of Industrial Engineers, 2014)
Planning and scheduling play very important role in health care. Effective scheduling optimizes the utilization of scarce resources such as surgeons, operating rooms, and devices in hospitals. The operating rooms are regarded as the hospital's engine, and they are considered among the most costly hospital facilities. This study presents a model for operating room resource scheduling. A mathematical model is developed for optimizing the performance measures (i.e., minimizing the number of unscheduled surgical operations). Using this model, we not only determine the allocation of surgeries to operating rooms but also the sequence of surgeries within operating rooms. The proposed model is tested using the real data obtained from a university research hospital in Turkey.
Amazon;Arena;Boeing;et al.;UFC;VirginiaTech - College of Engineering
IIE Annual Conference and Expo 2014 -- 31 May 2014 through 3 June 2014 -- -- 114710
Keywords: Health Care; Mathematical Programming; Operating Room; Scheduling And Planning; Health Care; Mathematical Models; Mathematical Programming; Operating Rooms; Surgery; Minimizing The Number Of; Performance Measure; Planning And Scheduling; Resource-Scheduling; Scarce Resources; Scheduling And Planning; Surgical Operation; University Research; Scheduling